2018
DOI: 10.1080/1331677x.2018.1498010
|View full text |Cite
|
Sign up to set email alerts
|

Corruption and shadow economy in transition economies of European Union countries: a panel cointegration and causality analysis

Abstract: Corruption and shadow economy are two critical problems which feed each other and pose an obstacle against the economic development of countries, especially those with weak fundamentals. Central and Eastern European countries have experienced an absolute political and economic transformation after the downfall of the Berlin Wall. This study researches the effect of corruption and rule of law on shadow economy in 11 transition economies of Central and Eastern Europe over the 2003-2015 term with panel cointegrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 19 publications
1
21
0
2
Order By: Relevance
“…Corruption is closely connected to other negative phenomena, such as fiscal evasion, as found by several authors [13,19]. In addition, corruption and fiscal evasion are complementary in low-income countries, as evidenced by other researchers [20,21].…”
Section: Literature Reviewmentioning
confidence: 80%
See 1 more Smart Citation
“…Corruption is closely connected to other negative phenomena, such as fiscal evasion, as found by several authors [13,19]. In addition, corruption and fiscal evasion are complementary in low-income countries, as evidenced by other researchers [20,21].…”
Section: Literature Reviewmentioning
confidence: 80%
“…The majority of reference literature papers revealed that corruption has a strong negative impact upon economic growth and upon the efficiency of economic activity [10][11][12][13][14]. Corruption negatively impacts private investments, employment rate, and income per capita [15].…”
Section: Literature Reviewmentioning
confidence: 99%
“…1 Corruption is one of the reasons for the high level of shadow economy in Bulgaria. Bayar et al (2018) demonstrated the empirical relationship between corruption, the shadow economy and the rule of law in the countries undergoing economic transition. The results of co-integration calculated on the basis of data for the 2003-2015 period indicate that the increase in the rule of law and anti-corruption policies has reduced the shadow economy.…”
Section: Resultsmentioning
confidence: 99%
“…The cointegration coefficients revealed a complementary interplay between the size of the shadow economy and corruption. Furthermore, the causality analysis indicated that there was a bilateral causality between control of corruption and the shadow economy in all the cross-section units (Bayar et al 2018).…”
Section: Literature Reviewmentioning
confidence: 93%